The Oxford handbook of politics and performance - Rai, Shirin 1960-; Gluhović, Milija 1971-; Jestrović, Silvija 1970-; Saward, Michael 1960- (Oxford handbooks online, 2021)
While political scientists and political theorists have long been interested in social and political performance, and theatre and performance researchers have often focused on the political dimensions of the live arts, the interdisciplinary nature of this labour has typically been assumed rather than rigorously explored. This volume brings together leading scholars in the fields of politics and performance - drawing on experts across the fields of literature, law, anthropology, sociology, psychology, and media and communiction, as well as politics and theatre and performance - to map out and deepen the evolving interdisciplinary engagement